2011
DOI: 10.2478/v10118-011-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Palynology of Late Pleistocene varved clays from ice-dammed lakes at Lębork and Złocieniec (north-western Poland) - preliminary results

Abstract: Samples collected from Late Pleistocene varved clays of the Vistulian (Weichselian) glaciation exposed at Lębork and Złocieniec (Gardno and Pomeranian phases, respectively) yielded palynological contents that are related to the different lithologies composing the varves. The dark-coloured clay units contain very small amounts of palynological material. The lighter-coloured, much thicker coarser units yielded large amounts of organic particles consisting of predominantly palynodebris of terrestrial plants, spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The occurrence of Cretaceous and Paleogene dinoflagellate cysts showed that sediments of these ages could also be reworked and redeposited as varved clays at Lębork. This may confirm a Tertiary origin of the quartz grains in the varves of the Lębork ice-dammed lake (Gedl 2011).…”
Section: Resultssupporting
confidence: 55%
“…The occurrence of Cretaceous and Paleogene dinoflagellate cysts showed that sediments of these ages could also be reworked and redeposited as varved clays at Lębork. This may confirm a Tertiary origin of the quartz grains in the varves of the Lębork ice-dammed lake (Gedl 2011).…”
Section: Resultssupporting
confidence: 55%
“…More oriented kettle holes are fairly common in western and middle Pomerania (Kozarski, 1975;Rachlewicz, 1991;Bukowska-Jania, 2003). These regions were, like northern Germany in the West (Pisarska-Jamroży & Börner, 2011) and the Mazury Lakelands in the East (Morawski, 2009a, b), also covered by ice during the Pomeranian phase of the Vistulian glaciation (Morawski, 2009b;Gedl, 2011).…”
Section: Fig 3 Study Sites (Background Frommentioning
confidence: 98%
“…Varved lake sediments have also been studied in Europe, where the focus was on seasonal variability of the late Weichselian and Holocene climate and corresponding changes in the flora and fauna (Goslar et al 1998;Chapron et al 2007;Voigt et al 2008;Gedl 2011). Abundant studies have described trace fossils (arthropod and fish trackways) from varved lacustrine sediments (Benner et al 2008;Uchman et al 2009), but few reports deal with crustaceans, especially from the end of the Saalian glaciations to the beginning of the Eemian interglacial (Mirosław-Grabowska et al 2009).…”
Section: Introductionmentioning
confidence: 99%